2011
DOI: 10.1038/oby.2010.152
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Long‐ or Medium‐Chain Fat Diets on Glucose Tolerance and Myocellular Content of Lipid Intermediates in Rats

Abstract: Accumulation of triacylglycerols (TAGs) and acylcarnitines in skeletal muscle upon high-fat (HF) feeding is the resultant of fatty acid uptake and oxidation and is associated with insulin resistance. As medium-chain fatty acids (MCFAs) are preferentially β-oxidized over long-chain fatty acids, we examined the effects of medium-chain TAGs (MCTs) and long-chain TAGs (LCTs) on muscle lipid storage and whole-body glucose tolerance. Rats fed a low-fat (LF), HFLCT, or an isocaloric HFMCT diet displayed a similar bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 49 publications
3
10
0
Order By: Relevance
“…However, several lines of investigation reported that MCFA-rich diets increased MCFA concentrations in the blood as well as several target organs including the skeletal muscle of rodents (8,24,25). The present study also showed that capric acid directly regulated UCP3 expression in skeletal muscle cells by an in vitro approach.…”
Section: Physiological Meaning Of Capric Acid-mediated Ucp3 Expressiosupporting
confidence: 61%
“…However, several lines of investigation reported that MCFA-rich diets increased MCFA concentrations in the blood as well as several target organs including the skeletal muscle of rodents (8,24,25). The present study also showed that capric acid directly regulated UCP3 expression in skeletal muscle cells by an in vitro approach.…”
Section: Physiological Meaning Of Capric Acid-mediated Ucp3 Expressiosupporting
confidence: 61%
“…Despite this reduction in whole-body insulin sensitivity, however, Turner et al (11) observed beneficial effects of the high-fat MCT diet on muscle fat accumulation and muscle insulin sensitivity, whereas liver insulin sensitivity was in fact similarly reduced upon both the MCT and the LCT diet. However, we have previously shown that 8 wk of highfat MCT vs. high-fat LCT feeding in mice resulted in a similar reduction in whole-body insulin resistance, despite dramatically lower lipid levels in both liver and skeletal muscle after the high-fat MCT diet (9). Intriguingly, and in contrast to the previously mentioned study by Turner et al (11), the reduction in whole-body insulin sensitivity upon the high-fat MCT diet was mainly accounted for by a reduced peripheral glucose uptake (primarily skeletal muscle), whereas liver insulin sensitivity appeared normal (9).…”
Section: Discussionmentioning
confidence: 88%
“…However, we have previously shown that 8 wk of highfat MCT vs. high-fat LCT feeding in mice resulted in a similar reduction in whole-body insulin resistance, despite dramatically lower lipid levels in both liver and skeletal muscle after the high-fat MCT diet (9). Intriguingly, and in contrast to the previously mentioned study by Turner et al (11), the reduction in whole-body insulin sensitivity upon the high-fat MCT diet was mainly accounted for by a reduced peripheral glucose uptake (primarily skeletal muscle), whereas liver insulin sensitivity appeared normal (9). The discrepancy in results between these two animal studies might be explained by the specific type of MCFA used in the respective studies; whereas the diets used by Turner et al (11) primarily contained fatty acids of 12 and 14 carbon atoms in chain length, we previously used fatty acids of shorter chain length (C8 and C10).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Yet, the in situ free concentrations of many metabolites, including acylcarnitines, are difficult to determine in tissues, and it is important to note that in our cell models acylcarnitines were applied in the culture media. With a rodent obesity models, muscle mediumchain fatty acid (MCFA) C14-carnitine moieties reach estimated concentrations of 5-10 M, with some LCFA-carnitine concentrations around 5-10 times higher (calculated from (3,7)). Furthermore, the total tissue concentrations of several acylcarnitines of longer chain length in mice were shown to be much greater than that of L-C14 carnitine used in our study (15).…”
Section: Discussionmentioning
confidence: 99%